Decomposed total factor productivity of Indonesian rice production - Joko Mariyono (Economic Journal of Emerging Markets, 2018)
Rice is still a staple food for the people of Indonesia. If Indonesia relies on imported rice, it will be very politically vulnerable if there is a shortage of rice supply in the international market. Therefore, the productivity of rice farming should be kept rising in line with the rate of population increase. This paper analyzes the growth of total factor productivity of paddy farming efforts. Total productivity is decomposed into four parts: the advancement of technology, technical efficiency, allocative efficiency and the effect of business scale. If each component of productivity growth is known, it will be determined strategies to increase rice production. Data analysis using secondary data published by the Indonsian Statistics Agency (BPS). Analyses were performed using an econometric approach. The results show that growth in total factor productivity declined with the slowdown. Positive contributor to the growth of total factor productivity is the change in the technical and business scale effects; whereas negative contributor is the technical and allocative efficiency. Growth in rice production is because of growth in the use of inputs and other factors such as the expansion and increase in cropping index. The growth in total factor productivity can be increased by improving technical and allocative efficiencies.